New and Old Samoyed Etymologies, Part 2 - Ante Aikio (Société Finno-Ougrienne, 2006)
This paper is a sequel to New and Old Samoyed Etymologies published in FUF 56, offering etymological equations between Samoyed and Finno-Ugric languages, including both new etymologies and arguments supporting previous comparisons that have not been accepted in the strictest modern treatments of the Proto-Uralic lexicon. A total of fourteen Samoyed word families are analyzed as inherited from Proto-Uralic.